Study on Gastrointestinal Nematodes of Equines in and around Bekoji, South Eastern Ethiopia - Mesfin Mathewos; Dereje Teshome; Haben Fesseha (Journal of Parasitology Research)
Parasitic infections can cause a variety of respiratory, intestinal, and other problems in horses, as well as contribute to some performance issues. A cross-sectional study was undertaken in and around Bekoji, South Eastern Ethiopia, from November 2020 to June 2021 to identify species and evaluate the prevalence of gastrointestinal parasites in donkeys and horses, using direct fecal smear, floatation methods, and larval cultures. In this study, the overall prevalence of gastrointestinal nematode parasites was 94.5% (363 out of 384), with donkeys accounting for 95.8% and horses accounting for 90.5%. The coprological study indicated that an overall prevalence of gastrointestinal nematode parasites was 87%, 8.3%, 2.5%, 1.4%, and 0.8% for mixed parasite infection, nonmigratory strongylids, migratory strongylids, Parascaris equorum, and Oxyuris equi, respectively. Among mixed infections, nonmigratory strongylids+migratory strongylids (51.5%) occurred most frequently. The odds of male horses being infected by GIT nematodes were 1.59 times higher than male donkeys. Horses which have poor body condition were 2.94 times more infected than donkeys. The odds of old-aged donkeys were 3.11 times more infected than horses. A statistically significant difference (p<0.05) was observed in the prevalence of gastrointestinal nematodes with species and body conditions of the animals. However, no statistically significant difference (p>0.05) was seen in the prevalence of gastrointestinal nematode parasites between the sex and age of the Equidae. The mean fecal egg count of nematodes revealed that horses (1364.4±483.5) had a more severe infection than donkeys with a statistically significant difference (p<0.05). The current study determined there was a high prevalence of gastrointestinal nematode parasites in Equidae. Regular deworming, improved housing and nutrition management systems, increased animal owner awareness, and prevention techniques should all be undertaken to minimize the disease’s economic burden in the area.